Profile of Quality of Comprehension and Mathematics Anxiety of Grade IX Students of MTs Negeri Karangasem on Building Materials for Curved Side Spaces - Maulida, Rahmiyati; Bondan Widjajanti, Djamilah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study aims to: (1) describe the quality of mathematical understanding of Grade IX students at MTs Negeri Karangasem on the topic of curved surface solids, (2) identify the level of mathematics anxiety, and (3) examine the relationship between mathematical understanding and mathematics anxiety. This research employed a quantitative approach involving 100 students selected from 130 Grade IX students. Mathematical understanding data were collected using a three-item test based on indicators of instrumental, relational, and logical understanding, while mathematics anxiety data were obtained through a 30-item questionnaire. All instruments were validated by experts and showed adequate reliability based on Cronbach’s Alpha. Data were analyzed using descriptive statistics, while the relationship between variables was tested using the Chi-Square test and the Fisher Freeman Halton Exact Test. The results show that most students (80%) have not yet achieved adequate mathematical understanding, while 20% demonstrate instrumental understanding. In terms of anxiety, 84% of students experience moderate anxiety, 11% high anxiety, and 5% low anxiety. Most students (67%) fall into the category of moderate anxiety with low understanding. Statistical results indicate that mathematical understanding and mathematics anxiety are significantly related.